El profesor migrante y su saber pedagógico. Autobiografías de maestros en condición de tercera edad (2020)
Starting from the epistemological horizon of the biographical-narrative method, it is proposed to analyze the processes of constitution of pedagogical knowledge linked to the teaching work and to the life trajectories of four migrant teachers in conditions of third age. The participants construct autobiographical texts that configure the experiences and meanings of their formative processes articulated to a multiple vital system that operates as the foundation of a broad and complex conception of pedagogical knowledge. From this point of view, the teachers’ life narratives are integrated into the training of new teachers from the redesign of workshops for the areas of Investigative Pedagogical Project and Deepening Practice, in the Faculty of Education of the UPTC. Finally, the characteristics of the teachers considered here, as migrants and senior citizens, hope to contribute to contemporary debates on education in the Colombian national context where it is not common to value the testimony of older adults in pedagogical actions and where the emerging migratory phenomenon confronts the ways of assuming plurality, coexistence and cultural exchange.